2013
DOI: 10.1093/aepp/ppt008
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Farm Size Growth? An Illustration in Southwestern France

Abstract: Farm size in industrialized countries grew significantly over the second half of the twentieth century. Using several econometric models, this article examines factors that influence farm size, the probability of an increase in farm size, and the intensity of farm growth. We find that farm structural characteristics, farmer's age, the existence of a successor, and spatial factors approximating urban influences have a significant impact on farm size, whereas human capital variables do not. This study considers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 28 publications
4
30
2
Order By: Relevance
“…Based on the coefficients of our regression models, we conclude that farm growth intentions are influenced primarily by structural characteristics such as relative farm size change in the past, current farm size and sunk costs proxied in our survey with stated overcapacities. This corresponds with our expectations since these factors are also decisive when analyzing observed farm structural change in general (Akimowicz et al, 2013, Breustedt and Glauben, 2007, Weiss, 1999 and also correspond with recent studies that assess future intentions of farmers under different policy settings and scenarios (e.g. Bartolini and Viaggi, 2013, Bougherara and Latruffe, 2010, Latruffe et al, 2013, Lobley and Butler, 2010, O'Donnell et al, 2011, Raggi et al, 2013.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Based on the coefficients of our regression models, we conclude that farm growth intentions are influenced primarily by structural characteristics such as relative farm size change in the past, current farm size and sunk costs proxied in our survey with stated overcapacities. This corresponds with our expectations since these factors are also decisive when analyzing observed farm structural change in general (Akimowicz et al, 2013, Breustedt and Glauben, 2007, Weiss, 1999 and also correspond with recent studies that assess future intentions of farmers under different policy settings and scenarios (e.g. Bartolini and Viaggi, 2013, Bougherara and Latruffe, 2010, Latruffe et al, 2013, Lobley and Butler, 2010, O'Donnell et al, 2011, Raggi et al, 2013.…”
Section: Discussionsupporting
confidence: 91%
“…Existing literature on ex-post analysis of structural change rooted in economic theory suggests multiple factors that influence the allocation of production factors, in particular the allocation of labor (reviews in Buchenrieder et al, 2007, Mann, 2003b, Zimmermann et al, 2009. In general, there are multiple drivers behind these processes including economic growth as a whole, adoption of new technology, off-farm employment, human (managerial) capital, market structure, investment constraints, social networks, as well as the existing policy environment (Akimowicz et al, 2013, Breustedt and Glauben, 2007, Chavas, 2001, Huettel and Margarian, 2009, Margarian, 2007, Storm et al, 2014, Weiss, 1999, Zimmermann and Heckelei, 2012.…”
Section: Drivers Of Structural Changementioning
confidence: 99%
See 1 more Smart Citation
“…Rizov and Mathijs (2003) found that an increase in human capital improves the effectiveness of farm operators in adopting new technologies, which can explain higher growth and survival rates. More recently, D' Amico et al (2013) argue that farming firms performance is related to the quality of human capital, while Akimowicz et al (2013) concluded that farmer-specific characteristics as a measure for human capital do not play a role on farm's size and growth. Villatoro and Langemeier (2006) also examined the factors that have impact on farm growth.…”
Section: Managerial Capabilities and Human Capital Investmentsmentioning
confidence: 99%
“…The enlargement of farm size of Kebumen PO cattle requires the improvement of technological mastery, provision of production input and provision of manpower abilities. Akimowicz et al (2013) state that age and experience as the farmer's individual potential variables influence the development of business scale. In addition, Ndege (2015) state education and training, skill and technology, and capital availability influence the development of small scale business.…”
Section: Farmer's Individual Potential In Various Farm Sizesmentioning
confidence: 99%